Application of the dredging method in a case of recurrent ameloblastoma that had spread over a large region of the mandible. Issue 1 (January 2020) - Kakuguchi, Wataru; Ohiro, Yoichi; Nakazawa, Seitaro; Naito, Ryo; Moritani, Yasuhito; Nakamichi, Yoshiyuki; Horimukai, Hiromasa; Kitamura, Tetsuya; Tei, Kanchu
Abstract: Ameloblastomas have a high post-surgical recurrence rate. They often recur after simple conservative surgeries, such as enucleation. The dredging method was thus developed as an alternative, conservative treatment of ameloblastoma. This method accelerates new bone formation and enables surgeons to remove all tumors, leading to lower recurrence rates than deflation and/or enucleation alone. However, no reports have examined whether the dredging method is effective in recurrent cases of ameloblastomas. A 49-year-old male was referred to our hospital due to right mandibular swelling. This patient had been treated for ameloblastoma with the dredging method until 25 years ago at our hospital. The patient was not seen again after 1 year from the last surgery. A clinical and histopathological diagnosis of recurrent ameloblastoma of the right mandible was made. We applied the dredging method, judging it to be adequate for tumor removal while preserving the jaw bone. A panoramic radiograph revealed mandibular bone restoration with each surgery and removal of all tumor cells had been completed. The patient was followed-up and no recurrence of ameloblastoma was found by 1.5 years following his final surgery. Additionally, the patient was permitted to wear dentures. In the present report, we show that the dredging method was applicable for a case of recurrent ameloblastoma that had spread over a large region of the mandible. The dredging method further allowed the patient to restore denture occlusion by preserving the jaw bone.